Synthesis and Estimate of Antimicrobial Efficacy of New Benzoic Acid Hydrazide Derivatives Substituted by Piperidine - Hussam Z.Naji; Ghosoun Lafta Mohsen (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Several of the best-selling small-molecule medications and natural alkaloids contain piperidine, a crucial saturated heterocyclic scaffold with a wide variety of biological functions. The hydrazide-hydrazone moiety's exceptional use in the pharmacological and biological domains made it particularly appealing. Objective: Designing and synthesizing a novel set of 4-Piperidin-1-yl-benzoic acid substituted hydrazides, Ac1-c3 and Bc1-c5, as potentially antimicrobial agents and characterizing them using IR, 1H-NMR, and mass spectroscopy. Methods: By esterifying 4- Piperidin-1-yl-benzoic acid Ac1 and then treating with hydrazine hydrate it to produce Ac3 in a good yield. The hydrazide Ac3 was condensed with the proper aldehydes or ketone to synthesis the hydrazones Bc1–c5. The in vitro bacterial activity was evaluated anti two Gram-negative bacteria, Pseudomonas aeruginosa, and Candida albicans, as well as two Gram-positive bacteria, Staphylococcus aureus and Bacillus subtilis. Results: The majority of tested compounds demonstrated significant efficacy anti Pseudomonas aeruginosa, Candida albicans. Notably, compound Bc3 emerged as the most effective derivative within the series. Conclusions: The Compounds (Bc1–c4) that were synthesized demonstrated moderate to good antimicrobial activity against a number of bacterias species and Candida albicans.